The Implementation of Web-Based Paperless Office Technology in the Final Project Information System at the Faculty of Engineering, Malikussaleh University - Razi, Ar; Yulisda, Desvina; Anshar, Khairul; Fikri, Ahmad (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
The final project information system application, often known as the final project management system, is a digital tool designed to assist the management and reporting process related to students' final projects. This system includes various features that can assist lecturers, students, and academic staff in various aspects of the final project process. This application allows students to submit their final project proposals, including uploading required documents such as study plans, final project proposals, and thesis reports. In addition, lecturers can also utilize features that allow lecturers to input grades and provide minutes for final project proposals submitted by students. This information system also allows the final project coordinator to manage the final project trial schedule, including scheduling and canceling schedules. In addition, the final project information system makes it easier to manage final project data, including student data, title data, and supervisor data. This facilitates the process of searching for titles and assigning supervisors, as well as speeding up the title validation process.